2010
DOI: 10.1590/s0100-40422010000200019
|View full text |Cite
|
Sign up to set email alerts
|

Otimização e validação de métodos analíticos para determinação de BTEX em água utilizando extração por headspace e microextração em fase sólida

Abstract: Recebido em 2/3/09; aceito em 18/8/09; publicado na web em 21/1/10 EVALUATION 0F ANALYTICAL METHODS FOR BTEX ANALYSIS IN WATER USING EXTRACTION BY HEADSPACE (HS) AND SOLID PHASE MICROEXTRACTION (SPME). Three analytical methods for the determination of BTEX in water were optimized and validated. With the best method the analytes were extracted of 10 mL of sample with 2.50 g of NaCl in headspace vial of 20 mL by HS and SPME to 40 o C for 30 min for adsorption and to 250 o C for 4 min for desorption and were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
2
0
6
Order By: Relevance
“…1A), which allowed better responses (i.e., larger peak areas) to be reached. These results are in accordance with those of Heleno et al [3] who showed the feasibility of BTEX extraction from waters by static HS followed by GC-FID analysis and observed that the optimal temperature was 80ЊC.…”
Section: Multivariate Optimization Of Btex Extractionsupporting
confidence: 93%
See 1 more Smart Citation
“…1A), which allowed better responses (i.e., larger peak areas) to be reached. These results are in accordance with those of Heleno et al [3] who showed the feasibility of BTEX extraction from waters by static HS followed by GC-FID analysis and observed that the optimal temperature was 80ЊC.…”
Section: Multivariate Optimization Of Btex Extractionsupporting
confidence: 93%
“…However, although there are, in the literature, many investigations on method development and validation for BTEX determination [3,12,17,18,20,23,25], very few used multivariate experimental design techniques in the extraction process optimization [3,23].…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, o risco de poder ocorrer vazamentos é extremamente grande (Castro e Branco, 2003). (WHO, 2010, Heleno, 2010. A movimentação e a distribuição dos contaminantes estão relacionadas com a pluviosidade, variações sazonais e o gradiente hidrológico da área (Daniels et al, 1995;Corseuil e Marins, 1997;Tiburtios et al, 2005).…”
Section: Introductionunclassified
“…Diversas técnicas de extração e pré-concentração de BTEX têm sido reportadas na literatura, como a extração headspace (HS), purga e trapeamento (purge and trap), microextração em gota única (single drop microextration: SDME), microextração em fase líquida com fibra oca (hollow fiber supported liquid-phase microextraction: HF-LPME), extração com membranas com uma interface sorvente (flat-sheet membrane extraction with a sorbent interface: MESI) e microextração em fase sólida (solid phase microextraction: SPME). [7][8][9][10][11][12][13][14][15][16][17] Purge and trap é a técnica utilizada na extração de BTEX no método oficial EPA 524.2 (PT-GC/MS) e os limites encontrados são similares aqueles determinados por microextração em fase sólida. 9,18 A determinação de BTEX em água por GC-FID com as técnicas de extração, HS estático e HS-SPME, foi estudada por Menéndez e colaboradores.…”
Section: Introductionunclassified
“…8 O método de extração HS-SPME e análise GC-MS mostrou melhores resultados para os parâmetros de validação no estudo comparativo com a técnica de headspace. 7 Para as técnicas SDME e HF-LPME em análise GC-FID foram observados limites de detecção para BTEX em água entre 0,8-7 µg L -1 e 2,7-4,0 µg L -1 .…”
Section: Introductionunclassified